Alleviating the Collision States and Fleet Optimization by Introducing a New Generation of Automated Guided Vehicle Systems - Parham Azimi (Modelling and Simulation in Engineering)
The aim of the current research is to propose a new generation of automated guided vehicle systems for alleviating the collision states in material handling systems where the automated guided vehicles movements are allowed to be both unidirectional and bidirectional. The objective function is to maximize the average annual profit in an FMS system using a simulation method. Despite several researches done in this field, this criterion has been studied rarely. The current study includes some new changes in AGV design for preventing some common problems such as congestions and deadlocks based on real profits/costs analysis in a flexible manufacturing system. For this reason, some experiments have been carried out to study the effects of several empty vehicle dispatching rules on average annual profit. The results show that the proposed framework is efficient and robust enough for industrial environments.